Estabelecendo uma string de busca para a identificação de estudos secundários na engenharia de software - Napoleão, Bianca Minetto (2019)
Context: Systematic Review and Systematic Mapping are examples of secondary studies. In general, these studies summarize different results related to a common research topic. Conducting secondary studies involves a detailed process. However, before beginning the process to conduct a secondary study it is fundamental to identify if there are already studies on the intended topic, avoiding was ting of time. In addition, secondary studies are the inputs of a tertiary study. A critical step in searching for secondary studies is the creation of a search string. Goal: The main goal of this work was to analyze search strings to establish directions to better detect secondary studies in Software Engineering (SE). Methodology: We analyzed tertiary studies under two perspectives: (1) structure–strings’ terms to detect secondary studies and (2) field: where searching–titles alone or abstracts alone or keywords alone or titles and abstracts together, among others. We also performed a validation of the results found. Results: The suitable search string for finding secondary studies in SE contain the terms “systematic review”, “literature review”, “systematic mapping”, “mapping study”, “systematic map”, “meta-analysis”, “survey” and “literature analysis”. Further more, we recommend (1) researchers use the title, abstract and keywords search fields in their searches to increase studies recall; (2) researchers choose carefully their paper title, abstract and key word terms to increase the chance of having such studies found on digital libraries. Conclusions: The search string applied on the search fields presented in this work efficiently returned 98.68% of the analyzed secondary studies. The search string, search fields and recommendations for writing titles, abstracts and keywords may provide a time-saving useful tool for SE researchers who need to analyze secondary studies.